The theoretical description of cathodic deposition of new conducting polymer composite, assisted by a perrhenate of a novel triazolic derivative - Tkach, V. V.; Kushnir, M. V.; Storoshchuk, N. M.; Parchenko, V. V.; Aksyonova, I. I.; Odyntsova, V. M.; Luganska, O. V.; Yagodynets, P. I.; Парченко, Володимир Володимирович; Аксьонова, Ілона Ігорівна; Одинцова, Віра Миколаївна (Brazil : Institute of Chemistry of the Universidade Federal de Mato Grosso do Sul, 2020)
Abstract: The theoretical description of a new sandwich-like rhenium-based polymer composite cathodic electrodeposition has been given. The cathodic process is realized by perrhenate-ion electrochemical reduction to rhenium (IV) oxide, acting as an in situ formed oxidant for 3,4-dimethoxypyrrole polymerization. It is shown that the polymer deposition in this system is realized by more efficient manner than during the direct electropolymerization. The polymer composite has to have a well-developed morphology and enhanced conductivity by sandwich-like structure. The oscillatory behavior, in this case, is also possible, being caused by the DEL influences on both electrochemical and chemical stages of the process.
Keywords: conducting polymer composites; rhenium; assisted polymerization; electrochemical oscillations; stable steady-state